Validating the Michigan Hand Outcomes Questionnaire in patients with rheumatoid arthritis using Rasch analysis. - Mayank Jayaram (Public Library of Science (PLoS), 2021)
Introduction The Michigan Hand Outcomes Questionnaire (MHQ) is a patient-reported outcome measure previously validated in patients with rheumatoid arthritis (RA) using classical test theory. Rasch analysis is a more rigorous method of questionnaire validation that has not been used to test the psychometric properties of the MHQ in patients with RA. The objective of this study is to evaluate the validity and reliability of the MHQ for measuring outcomes in patients with RA with metacarpophalangeal joint deformities. Methods We performed a Rasch analysis using baseline data from the Silicone Arthroplasty in Rheumatoid Arthritis (SARA) prospective cohort study. All domains were tested for threshold ordering, item fit, targeting, differential-item functioning, unidimensionality, and internal consistency. Results The Function and Work domains showed excellent fit to the Rasch model. After making adjustments, the Pain, Activities of Daily Living (ADL) and Satisfaction domains also fulfilled all Rasch model criteria. The Aesthetics domain met the majority of Rasch criteria, but could not be tested for unidimensionality. Conclusions After collapsing disordered thresholds and removing misfitting items, the MHQ demonstrated reliability and validity for assessing outcomes in patients with RA with metacarpophalangeal joint deformities. These results suggest that interpreting individual domain scores may provide more insight into a patient's condition rather than analyzing an overall MHQ summary score. However, more Rasch analyses are needed in other RA populations before making adjustments to the MHQ.